The Contribution of App Inventor 2-Based Teaching Materials to Economic Learning Independence and Outcomes through Self-Efficacy - Baiq Yuliana Rizkiwati; Muhammad Zainul Majdi; Yati Yati (Economics Education Department Universitas Negeri Semarang, 2025)
This study examines the contribution of App Inventor 2-based economics teaching materials to student learning independence and learning outcomes, mediated by self-efficacy. Employing a quantitative explanatory approach with causality design and path analysis, the research involved 32 tenth-grade students from SMK-IP YADARO Moyot selected through simple random sampling. Data collected via tests and questionnaires were analyzed using AMOS version 23. The measurement model demonstrated good fit with CFI and GFI values of 1.00, a significant chi-square value, and an acceptable RMSEA of 0.062, supported by other fit indicators. The absence of multicollinearity confirmed the independent contributions of each variable. App Inventor 2-based teaching materials showed significant direct effects on both self-efficacy and learning independence. Furthermore, both self-efficacy and learning independence significantly influenced students’ economics learning outcomes. Path analysis revealed an important indirect effect, where teaching materials impacted learning outcomes through mediation by self-efficacy. These findings highlight the crucial integration of learning technology and psychological factors in enhancing educational quality, suggesting that technology-based materials contribute not only directly but also through strengthening students’ belief in their capabilities, ultimately improving learning outcomes in economics education. The research highlights the importance of integrating technological innovation with psychological support in developing effective learning environments.